Electrical transport and optical model of GaAs-AlInP core-shell nanowires - Chia, A. C. E. (2012)
GaAs nanowires were passivated by AlInP shells grown by the Au-assisted vapor-liquid-solid method in a gas source molecular beam epitaxy system. Transmission electron microscopy confirmed a core-shell GaAs-AlInP structure. Current-voltage measurements on ensemble nanowires indicated improved carrier transport properties in the passivated nanowires as compared to their unpassivated counterpart. Similarly, individual nanowires showed improved photoluminescence intensity upon passivation. A detailed model is presented to quantify the observed improvements in nanowire conduction and luminescence in terms of a reduction in surface charge trap density and surface recombination velocity upon passivation. The model includes the effects of high-level injection, bulk recombination, and surface recombination. The model can be used as a tool for assessing various passivation methods. © 2012 American Institute of Physics.